Iowa RBA, August 11, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for August 11, 1997. Highlights of the update include sightings of a Roseate Spoonbill, a Black-headed Grosbeak, a Pacific Loon, and a Red-necked Phalarope. Other sightings of note were 6 Snowy Egrets, 27 Little Blue Herons, and 7 Yellow-crowned Herons east of Nebraska City. Also included are handwritten notes for the next week's update with sightings of Swainson's Hawks and an Ibis species. Epson - sheet feed/flatbed